'Split posterior tooth': conservative clinical re-attachment. (30th July 2014) - Abraham, Sathish; Chacko, Lisa Neelathil
Abstract : Trauma is the prime causative factor for fracture of teeth/dentition. Many procedural management options are followed successfully in relation to the anterior teeth. However, most posterior cases where the tooth is fractured have only limited options to pursue to save the tooth. Fractured teeth, whether they are vital/non-vital, are predominantly managed with surgical options. This paper discusses a conservative approach to reattaching a split posterior tooth. A split tooth situation is mostly an absolute indication for extraction, but the clinician may go in for extensive surgical procedures if he/she wishes to save it. The reattachment of the tooth can be successfully done and it can be put to function. This paper discusses how a split posterior tooth can be treated successfully, although depending on multiple factors. A full crown cemented after successful reattachment and root canal therapy would provide sufficient support in order for the tooth to heal.